Molecular docking studies of Pyranose-2-oxidase from trametes multicolor - Noorbatcha, Ibrahim Ali; Nuge, Tamrin; Yusof, Amirulakmal; Othman, Raihan; Mohd. Salleh, Hamzah (2013)
Pyranose 2-oxidase (P2Ox) is a FAD dependent enzyme widespread in wood-degrading basidiomycetes. P2Ox has several biotechnological applications, especially in biofuel cells (BFCs). In this research, computational protein design approach is used to design the new variants of P2Ox in order to improve the binding activity of P2Ox from Trametes multicolor (TmP2Ox) for further development of powerful BFCs. As a first step, the active site of P2Ox is identified by analyzing crystal structure of the enzyme complexed with the substrate. Then this active site is validated by automated docking of the substrates and comparing the docking score with the experimental results. Lamarckian genetic algorithm (LGA) is used to search for active sites and potential mean force (PMF) scoring method is used to evaluate different binding sites. The docking of minimum energy sugar conformation and strength of the binding (docking score) was evaluated using potential mean force (PMF) scores. β-D-Glucose, β-D-Galactose, β-D-Xylose, β-D-Allose and β-L-Arabinose were chosen as sugar substrates to investigate the substrate selectivity of wild type TmP2Ox (wtTmP2Ox). β-D-Glucose showed higher docking score compared to the others. The predicted docking scores were found to correlate very well with the experimental binding constant (Km) values with correlation coefficient R2=0.8744. In silico mutations were applied on several residue positions in the wtTmP2Ox to improve the binding activity. The effect of these mutations on binding strength was found to be in good agreement with experimental results.